Effects of Vessel Interruption Sequence During Lobectomy for Non-small Cell Lung Cancer: A Systematic Review and Meta-Analysis - Long, Xiang; Wu, Bingxuan; Zhang, Wenxiong; Lv, Guoli; Yu, Dongliang; Peng, Jinhua; Wei, Yiping; Lei, Youming (Frontiers in Surgery, 2021)
Background: For lobectomy in non-small cell lung cancer (NSCLC), whether interrupting the pulmonary vein first (Vein-first) achieves better perioperative and survival outcomes than interrupting the pulmonary artery first (Artery-first) remains controversial. We conducted this meta-analysis to compare outcomes between the two groups to facilitate better surgical decision-making. Methods: Web of Science, EMBASE, Cochrane Library, Ovid MEDLINE, PubMed, ScienceDirect, and Scopus were searched for eligible studies comparing Vein-first and Artery-first procedures. The primary endpoints were survival indicators [overall survival (OS), disease-free survival (DFS), and lung cancer-specific survival (LCSS)]. Secondary endpoints included intraoperative indicators, hospitalization, and follow-up indicators. Results: After screening 2,505 studies, 8 studies involving 1,714 patients (Vein-First group: 881 patients; Artery-first group: 833 patients) were included. The vein-first group achieved better OS [HR (hazard ratio): 1.46, 95% confidence interval (CI): 1.12–1.91, p = 0.005], DFS (HR: 1.60, 95% CI: 1.23–2.08, p < 0.001), and LCSS (HR: 1.64, 95% CI: 1.16–2.31, p = 0.005). The survival rates of OS at 2–5 years, DFS at 1–5 years, and LCSS at 3–5 years were also higher in the Vein-First group. Subgroup analyses suggested that the advantages of survival in the Vein-First group were primarily embodied in the subgroups of squamous cell carcinoma (SCC) and earlier pathological TNM stage (I–II). Operative time, intraoperative blood loss, total complications, and total recurrences were comparable between the two groups. Conclusions: The Vein-first sequence is the suitable choice of vessel interruption sequence during lobectomy for NSCLC with better survival and similar perioperative outcomes, especially for stage I–II SCC.